2014
DOI: 10.1089/pop.2013.0096
|View full text |Cite
|
Sign up to set email alerts
|

Economic Utility of a Blood-Based Genomic Test for the Assessment of Patients with Symptoms Suggestive of Obstructive Coronary Artery Disease

Abstract: Approximately 3 million patients with symptoms suggestive of obstructive coronary artery disease (CAD) present to primary care offices in the United States annually, resulting in approximately $6.7 billion in cardiac workup costs. Despite wide application of existing diagnostic technologies, yield of obstructive CAD at invasive coronary angiography (ICA) is low. This study used a decision analysis model to assess the economic utility of a novel gene expression score (GES) for the diagnosis of obstructive CAD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Lastly, our findings may have implications for risk avoidance for patients (by decreasing exposure to radiation and contrast agents) and economic utility for health care systems (through more cost-effective care and decreased overall health expenditures). [26][27][28][29][30][31][32] Our study has several limitations. The absence of a control group in the PRESET Registry limits direct comparisons with usual care, although our multivariate logistic regression analyses indicated a significant association between low ASGES and decreased cardiac referrals, beyond any effects on referral rates due to important demographic and clinical characteristics.…”
Section: E15mentioning
confidence: 95%
“…Lastly, our findings may have implications for risk avoidance for patients (by decreasing exposure to radiation and contrast agents) and economic utility for health care systems (through more cost-effective care and decreased overall health expenditures). [26][27][28][29][30][31][32] Our study has several limitations. The absence of a control group in the PRESET Registry limits direct comparisons with usual care, although our multivariate logistic regression analyses indicated a significant association between low ASGES and decreased cardiac referrals, beyond any effects on referral rates due to important demographic and clinical characteristics.…”
Section: E15mentioning
confidence: 95%
“…24–27 From a societal perspective, the ASGES has been shown to be cost-effective and may reduce overall health care expenditures. 28,29, 30…”
Section: Discussionmentioning
confidence: 99%
“…8 There is growing acceptance of genomic testing, particularly as it relates to cancer risk. 40 With the growing acceptance of applied genomics or ''precision medicine,'' the timing and environment seem appropriate for the incorporation of a new diagnostic aid for obstructive CAD that incorporates age, sex, and gene expression inputs to help inform the diagnostic and treatment pathway. The evidence base for the ASGES test is promising.…”
Section: Panel Discussion and Policy Recommendationsmentioning
confidence: 99%
“…8 A cost analysis revealed that substantially fewer nuclear stress MPI tests (4008 vs. 5200) and ICA tests (1742 vs. 2179) would be performed on patients whose risk of obstructive CAD had previously been assessed by an ASGES test and who had low scores. 40 This budget impact modeling study concluded that use of the ASGES test could be associated with costs savings of $0.77 per member per month.…”
Section: Personalized Risk Evaluation and Diagnosis In Thementioning
confidence: 99%